The Analysis Of The Implementation Of The Healthy Living Community Movement (Germas) Program In The Work Area Of The Hutabaginda Community Health Center, North Tapanuli Regency - Aritonang, Esra Puspita; Lubis, Basyariah; Br Girsang, Desri Meriahta (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: GERMAS is an effort to increase awareness, will and ability for everyone to live healthily so that the highest level of public health can be achieved (Ministry of Health of the Republic of Indonesia, 2017). GERMAS prioritizes promotive and preventive efforts, without neglecting curative-rehabilitative efforts by involving all components of the nation in promoting a healthy paradigm.Objectives: to describe and analyze the implementation of the GERMAS program in the Hutabaginda Community Health Center Working Area, North Tapanuli Regency.Research method: This type of research uses descriptive qualitative.Results: that the process of conveying policy information from policy makers to policy implementors is carried out in a structured manner. That the implementation of the GERMAS program in the Working Area of the Hutabaginda Community Health Center, North Tapanuli Regency, the Working Area of the Hutabaginda Community Health Center, Tapanuli Regency has been supported by adequate facility resources and village fund resources but has not been supported optimally by human resources. That cross-program and cross-sector coordination and cooperation in implementing the GERMAS program in the Working Area of the Hutabaginda Community Health Center, North Tapanuli Regency has shown a high level of commitment to realizing, supporting and implementing the GERMAS program in the Working Area Hutabaginda Health Center, North Tapanuli Regency. That the implementation of the GERMAS program policy in the Hutabaginda Community Health Center Working Area, North Tapanuli Regency has been carried out based on a hierarchical organizational structure and has been equipped with Standard Operating Procedures (SOP).Conclusion: The main inhibiting factor in implementing the GERMAS program policy in the Working Area of the Hutabaginda Community Health Center, North Tapanuli Regency is that the entire community does not regularly participate in activities carried out by Germas because there are still those who live in areas that are difficult to reach.